Naphthoate based lubricating oil with high oxidation stability and lubricity. (October 2019) - Fan, Mingjin; Ai, Jia; Hu, Chenghong; Du, Xin; Zhou, Feng; Liu, Weimin
Abstract: In this paper, we present the synthesis and tribological properties of two naphthatate-based lubricating oils. The structure and purity of the oils were analyzed using nuclear magnetic resonance spectra and high resolution mass spectra. Their thermal and oxidation stability, flash point and pour point, viscosity and viscosity index, and friction reduction and anti-wear properties were also tested. In the results, the two isooctyl naphthatate-based oils (INA) displayed better lubricating properties than a reference sample of isooctyl sebacate (ISE) on three different friction pairs. The new oils also offered higher oxidation stability than the reference sample. It was found that the stability and lubrication properties of ester-based lubricating oils can be significantly improved by introducing a naphthalene ring into the molecular structure. This is because there is a large π-electron conjugate system on the naphthalene ring, which not only reduces the likelihood of an oxidation chain reaction, but also enables the oil to form an orderly and stable lubricating film on metal surfaces. One of the oils, 2, 3-INA, was found have better oxidation stability than the other one, 1, 4-INA, because its oxidized groups are positively affected by the steric and conjugation effects of the two ester groups. Graphical abstract: Two new types of ester lubricating oil isooctyl naphthatate (INA) were synthesized. Due to the presence of multiple ester groups and naphthalene rings in the molecular structure, it shows better friction reducing and anti-wear properties than the reference sample isooctyl sebacate (ISE). More importantly, it exhibits remarkably higher oxidation stability than the reference sample.Image 1 Highlights: Isooctyl naphthatate (INA) were synthesized from Naphthalene dicarboxylic acid and isooctanol through esterification. 2, 3-INA and 1, 4-INA showed good friction reducing and anti-wear properties on three different friction pairs. 2, 3-INA and 1, 4-INA have excellent oxidation stability due to the presence of a naphthalene ring in the molecule.